Morphological and Molecular Identification of Saurida spp. (Teleostei: Synodontidae) from Saudi Arabia and Indonesia - Santanumurti, Muhammad Browijoyo; Suciyono, Suciyono; Abu El-Regal, Mohamed Ahmed (Makara Journal of Science, 2024)
Saurida is a unique fishery commodity because it is difficult to differentiate visually. They can be only effectively con-served once accurately identified. This study aimed to determine the morphology and molecular characteristics of Sau-rida spp. from Banyuwangi (Indonesia) and Jizan (Saudi Arabia). Meristic and morphometric analysis was performed for morphological identification, whereas COI gene analysis was performed for molecular identification. Morphological analysis was performed to identify Saurida in this study, such as S. tumbil (Jizan, Saudi Arabia) and S. micropectoralis (Banyuwangi, Indonesia). S. tumbil did not have dark brown spots on the lateral line and upper caudal fin, whereas S. micropectoralis had 6–9 spots on those parts. S. tumbil also had a larger body size, white intestines, and more dorsal fin spines, and its pectoral fin could reach the pelvic fin. This was different with S. micropectoralis, which had a smaller body size, black intestines, and fewer dorsal fin spines, and its pectoral fin was far from the pelvic fin. Molecular identi-fication showed 100% of S. tumbil for the sample from Jizan and 99.84% S. micropectoralis for the sample from Banyuwangi. Morphological and molecular characteristics can be combined for Saurida identification to avoid misi-dentification for future studies.